PAHs and fullerenes as structural and compositional motifs tracing and distinguishing organic carbon from soot. (1st February 2022) - Apicella, B.; Russo, C.; Carpentieri, A.; Tregrossi, A.; Ciajolo, A.
Graphical abstract: Highlights: Mass spectrometry for characterizing bimodality of organic carbon mass distribution. High laser power for inferring structural motifs discriminating large PAHs and soot. Fullerenes formation from PAHs and soot at high laser power in LDIMS spectra. Abstract: Examining the features distinguishing organic carbon from soot is crucial for understanding the source, the effect on the environment and their respective role in aerosol chemistry and soot formation. Beside to the obvious PAH picking-out in the low-mass mode (C number < 40), the challenging identification of PAHs in the high-mass mode (C number > 40) of organic carbon, separated by carbon particulate matter extraction from young and mature soot thermophoretically sampled in premixed flames, was done by laser-desorption-time-of-flight mass spectrometry, exploiting the laser power increase. The perusal of organic carbon mass spectra through mathematical tools in comparison to aromatic and alkyl-substituted PAH-laden samples and the persistence of high-mass mode at high laser power led to exclude the contribution of dimers and alkyl-bridged PAHs attributing the second mode to both fully-benzenoid and cyclopenta-PAHs. Profound differences between mass spectra of organic carbon and soot were noticed as neither molecules nor radicals of PAHs could be drawn out from soot, even at high laser power, and only small radicals and carbon clusters like fullerenes were observed, especially for young soot. These inferences evidenced the importance of analysing separately organic carbon and soot especially if insights into soot particles nucleation are to be obtained. In the case of benzene flame, already at the inception, soot consists of strongly tangled aromatic motifs crosslinked each other, presumably deriving from reactive coagulation/clustering of relatively small aromatic hydrocarbons/radicals early formed. In methane and ethylene flames, coalesced liquid-like material composed of soot and PAHs is formed and transformed later on undergoing some carbonization and molecular growth, respectively.